Checklist of the oribatid mites (Acari: Oribatida) of the Republic of Colombia - Salazar-Fillippo, Andrés A.; Miko, Ladislav (Zootaxa, 2022)
This checklist of oribatid mites of the Republic of Colombia compiles and provides a taxonomic update of all records known up to 2020. It includes 192 entries accounting for 68 named and 47 unnamed species belonging to 73 genera and 58 families of non-astigmatid oribatid mites. Specimens from the brachypyline supercohort were dominant (54.7%), followed by Mixonomata (30.7%). However, current knowledge is far from being complete and distribution patterns show large gaps throughout the country due to this lacking knowledge and most existing investigations only include group specific studies that prevent from any conclusions regarding the real community composition of oribatids in Colombia. From 32 political-administrative departments, oribatids have been reported in 20, but 5 account for 65% of the records. These are: Cundinamarca -including Bogotá D.C.- (24.4%), Magdalena (21.8%), Nariño (6.3%), La Guajira (6.3%), and Quindío (5.9%). Whereas most oribatid reports in the Neotropical region have taken place during the past five decades, a map presented in this document shows that Colombia still lags behind other Latin American countries. Mexico, Argentina, and Brazil, for instance, have reported the highest number of species for the region and are the only nations that possess national oribatid checklists in Latin America. The current work represents a national baseline of oribatids encouraging further study of this clearly underrepresented group.